Al-Sharif Al-Rdai and the his Ambition for Succession, in The Time of the Caliph Al-Qadir (359-401AH/ 969-1015) - Hindawi, Hanadi (Dirasat: Human and Social Sciences, 2019)
The research deals with al-Shrif al-Radi, Abu Al- Hasan , Muhmmad Ibn al-Hussein (359AH/ 965AD) and his efforts to take over the caliphate, as well as his biography.The research monitors the role of some political leaders in helping al-Sharif al-Radi to assume the caliphate including Abu al-Hassan al-Musawi. This research follows their contributions and influences. Additionally, this study examines the impact of education on the personality of al-Sharif al-Radi, his aspiration to the caliphate, his view of his era, the status of Abbasid caliphate, his vision of the weaknesses, and the impact of some personalities in his educational composition.This research deals with the manifestation of al-Radi’s aspirations found in his poems, his massages with the Sabee - one of al-Radi’s friends, and his close relationship with the Boheen. It also deals with his threats to move to Egypt, and insisting on not signing the record of the appeal to the Fatimids. The research discusses his relationship with the caliph al-Qadir Billah boasting with his lineage and claiming no difference between him and the caliph but the caliphate, as if he wants to say that al-Tha’alibis are more worthy of the Imamate than the Abbasid.